Estudo comparativo de resistência ao cisalhamento em reconstruções com amálgama, utilizando como procedimento retentivo pino rosqueável, amalgapin e adesivo dentário - Naressi, Suely Carvalho Mutti [UNESP] (1995)
In order to avoid the loss of largely destroyed crowns of posterior teeth, this study dealt with laboratory tests to compare the resistance to shear strengths application among three retentive procedures for amalgam buildups: adhesive amalgam, amalgapin and threadned pin. The failures resultant from the strength action, analysed visually and stereoscopic otic microscopy, permitted to conclude that the best retentive procedure happened with threadned pin, followed by amalgapin. The adhesive amalgam restoration technique was considered non-efficient, for the adhesive used, as the only retentive procedure in this kind of buildup